Loyalty and liberty : American countersubversion from World War I to the McCarthy era - Goodall, Alex (Alexis Vere) (Urbana : University of Illinois Press, 2013)
"Loyalty and Liberty offers the first comprehensive account of the politics of countersubversion in the United States prior to the McCarthy era. A sweeping study that surveys the loyalty politics of World War I, the antiradicalism of the 1920s and antifascism of the 1930s, and the emerging McCarthyite politics of World War II, this book shows how countersubversive thinking evolved alongside and contributed to the development of the modern federal state. Alex Goodall explores how antiradical crusading was hampered in the 1920s both by constitutional, financial, and political constraints on antisubversion that followed from excesses of political repression during and after World War I and by scandals that plagued the movement and led many to view it as either deluded or malevolent. The 1930s saw a major restructuring within the antiradical community, and New Deal activism encouraged a conservative backlash that began to see the looming threat of communism as lying in Washington, rather than on the margins of American society. Meanwhile, the executive branch created countersubversive machinery capable for the first time of prosecuting an effective war on radical dissent. By the end of World War II, new alliances on the left and right had largely consolidated into the form they would keep during the Cold War: a new anticommunist movement worked to restrain the supposedly dictatorial ambitions of the Roosevelt administration, while New Deal liberals split between supporters of the Popular Front, civil liberties activists, and embryonic Cold Warriors as they struggled to respond to the issues of communist espionage in Washington and communist influence in politics more broadly"--
part I. The revolutionary challenge -- part II. Professional patriots -- part III. The new anticommunism.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2013. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Anti-communist movements -- United States -- History -- 20th century; Radicalism -- United States -- History -- 20th century; Political persecution -- United States -- History -- 20th century; United States -- Politics and government -- 1919-1933.; United States -- Politics and government -- 1933-1945.; Electronic books